The debate on labor standards and international trade: Lessons from Cambodia and Bangladesh - Günseli Berik; Yana van der Meulen Rodgers (The University of Utah, Department of Economics, 2008)
This study examines the status and enforcement of labor standards in two Asian economies (Cambodia and Bangladesh) that are experiencing strong pressures to cut labor costs and improve the price competitiveness of their textile and garment exports. Analysis of survey, interview, and compliance data indicate differing trajectories in compliance with basic labor standards. While problems persist in Bangladesh, compliance has improved in Cambodia following a trade agreement with the United States that linked positive trade incentives with labor standards enforcement. These contrasting experiences suggest that trade-linked schemes can achieve improvements in labor standards without hindering export growth or job growth.
Keywords: 330; working conditions; enforcement; labor laws; female workers; gender and trade